CHILDHOOD EXPERIENCES IN PAINTINGS: EXPRESSIONS BY CONTEMPORARY INDIAN ARTISTS - Sharma, Tarun Kumar; Parvez, Shahid (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The present paper is an attempt to understand the relationship between the childhood experiences and its expression in visual art mediums such as painting, sculptures, and installations. Visual art is an important medium by which the subconscious mind finds its way for expression. In this research, some Indian contemporary artists have been studied on two parameters: first on their artwork and second on their childhood experiences. An attempt is being made to find out how the childhood experiences made an impact on their work. Both positive and negative experiences in childhood lead to creative pathways in an artist. The childhood experiences of these artists range from early demise of mother resulting in missing visage in paintings, to expression of darkness and death due to witnessing riots. The work of some artists who were abandoned ‘pink’ color due to dark complexion resulting in series of artwork titled ‘I hate pink’ or having positive experiences such as time spent with family being expressed in the form of family gathering paintings, are also elaborated in this paper. Psychologists have been finding ways to reach to the core of people’s mind to gain insight about the mental health issues and its causes or origins for an individual. The understanding of an individual’s artwork can be a way of identifying and understanding the expressions and reflections of that individual in drawings, paintings, and other visual art mediums.